СОЗДАНИЕ ВЕРОЯТНОСТНО-СТАТИСТИЧЕСКОЙ МОДЕЛИ КАЗАХСКОГО ТЕКСТА («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Currently, linguistic statistics is moving from its initial stage of describing linguistic phenomena to developing theories capable of quantitatively predicting language patterns. The main task of the study is to analyze the mathematical distribution of linguistic units in texts, which is key to modeling language phenomena. This research investigated the statistical distribution of major parts of speech in texts in the Kazakh language, including thousands of word usages from M. Auezov's novel "The Path of Abai" and newspaper texts. Using methods of mathematical statistics such as normal distribution, Poisson distribution, and Charlier distribution, theoretical patterns of distribution of these parts of speech were examined and confirmed. The experiments revealed significant features in the distribution of linguistic elements, contributing to a deeper understanding of the structure of language and its functioning in various contexts.
Keywords: linguistic statistics, mathematical distribution, Kazakh language texts, parts of speech, Poisson distribution, Normal distribution, language modeling.